Behavior of Halogen Bonds of the Y−X⋅⋅⋅π Type (X, Y=F, Cl, Br, I) in the Benzene π System, Elucidated by Using a Quantum Theory of Atoms in Molecules Dual‐Functional Analysis. Issue 16 (7th June 2016) - Sugibayashi, Yuji; Hayashi, Satoko; Nakanishi, Waro
Abstract: The nature of halogen bonds of the Y−X‐✶‐π(C6 H6 ) type (X, Y=F, Cl, Br, and I) have been elucidated by using the quantum theory of atoms in molecules (QTAIM) dual‐functional analysis (QTAIM‐DFA), which we proposed recently. Asterisks (✶) emphasize the presence of bond‐critical points (BCPs) in the interactions in question. Total electron energy densities, H b ( r c ), are plotted versus H b ( r c )− V b ( r c )/2 [=(ħ 2 /8 m )∇ 2 ρ b ( r c )] for the interactions in QTAIM‐DFA, in which V b ( r c ) are potential energy densities at the BCPs. Data for perturbed structures around fully optimized structures were used for the plots, in addition to those of the fully optimized ones. The plots were analyzed by using the polar ( R, θ ) coordinate for the data of fully optimized structures with ( θ p, κ p ) for those that contained the perturbed structures; θ p corresponds to the tangent line of the plot and κ p is the curvature. Whereas ( R, θ ) corresponds to the static nature, ( θ p, κ p ) represents the dynamic nature of the interactions. All interactions in Y−X‐✶‐π(C6 H6 ) are classified by pure closed‐shell interactions and characterized to have vdW nature, except for Y−I‐✶‐π(C6 H6 ) (Y=F, Cl, Br) and F−Br‐✶‐π(C6 H6 ), which have typical hydrogen‐bond nature without covalency. I−I‐✶‐π(C6 H6 ) has a borderline nature between the two. Y−F‐✶‐π(C6 H6 ) (Y=Br, I) were optimized as bent forms, in which Y‐✶‐π interactions were detected. The Y‐✶‐π interactions in the bent forms are predicted to be substantially weaker than those in the linear F−Y‐✶‐π(C6 H6 ) forms. Abstract : Nature of the bond : Linear Y−X‐✶‐π(C6 H6 ) interactions (X, Y=F, Cl, Br, I) are predicted to have typical hydrogen‐bond nature without covalency for Y−X=F−Br, F−I, Cl−I, and Br−I, and van der Waals (vdW) nature for the others by applying quantum theory of atoms in molecules dual‐functional analysis, whereas a vdW nature is found for all bent Y−F‐✶‐π(C6 H6 ) interactions (Y=Cl and Br).